PELAKSANAAN RENCANA PEMBELAJARAN SEMESTER DALAM PROSES PEMBELAJARAN DI PERGURUAN TINGGI - B.P. Sitepu; Ika Lestari (Perspektif Ilmu Pendidikan, 2018)
Higher-education curriculum is contained in Semester Learning Plan (RPS) as stated in Permenristekdikti No. 44 of 2015. RPS should bind lecturers and students into the contract of study/ college so that it needs to be supervised and examination of the quality of RPS made by lecturers. The purpose of this study is to conduct surveys and observations within the Fakultas Ilmu Pendidikan, Universitas Negeri Jakarta to obtain complete and accurate data and information. Referring to its purpose, this research includes descriptive evaluative research using qualitative and quantitative data. Data collection techniques used questionnaires, interviews, and document studies. Data is processed and analyzed using simple and descriptive statistics. The research was conducted in the Fakultas Ilmu Pendidikan, Universitas Negeri Jakarta in 2017. The results from the research are the percentage of lecturers to make RPS, student involvement in refining RPS, RPS utilization for students, students' knowledge on the subject and learning objectives during the course, and the references used. Further recommendations can be evaluated on the content of RPS made by lecturers in accordance with Permenristekdikti No. 44 of 2015. References Boak, G. (1998). A complete guide to learning contract. Aldershot: Gower. Evans, T. & Nation, D. (2000). Changing university teaching: Reflection on creating educational technology. London: Kogan Page. Harvey, L. & Knight, P.T. (1996). Transforming higher education. Buckingham: SRHE and University Press. Hussey, T. & Smith, P. (2010). The trouble with higher education: A critical examination of our universities. New York: Routledge. McNeil, J.D. (1996). Curriculum: A comprehensive in-troduction. New York: HarperCollins College Publishers. Reigeluth, M. C. (1983). Instructional-design theories and models, An overview of their current status. New jersey: London. Sanjaya, W. (2009). Strategi pembelajaran berorientasi standar proses pendidikan. Jakarta: Prenada Shattock, M. (2004). Managing successful universities. Berkshire: SRHE and University Press. Suciati. (2001). Kontrak perkuliahan. Jakarta: PAUPPAI-UT. Tyler, R.W. (1949). Basic principles of curriculum and instruction. Chicago: The University of Chicago Press. Permendikbud No 49 Tahun 2014 Permenristekdikti No 13 Tahun 2015 Permenristekdikti No 44 Tahun 2015 Peraturan pemerintah No 19 Tahun 2005